A Study of Sexual Dimorphism of Femoral Head In Gujarat Region - Pandya, A M; Gupta, B D; Singel, T C; Patel , M P (Journal of Indian Academy of Forensic Medicine, 2012)
Various diameters of head of femur have been in use for sex determination. These diameters  vary region wise also. Therefore we undertook the study in Jamnagar region of Gujarat. Maximum  diameter of the femoral head was measured in 184 dry, normal, adult, human femora (136 male & 48  female) obtained from M. P. Shah Medical College Jamnagar Gujarat. Mean Values obtained were, 43.75  and 40.33 for right male and female, and 43.88 and 40.64 for left male and female respectively. Higher  value in male was statistically highly significant (P< 0.001) on both sides. The data was subjected to  demarking point (D.P.) analysis. Maximum head diameter identified 11.90% of right male femora and  7.25% of left male femora; in female it identified 4% of left female femora while it was not useful (0.00%)  for right female bone. Though the sex of the bone can be determined from head of the femur bone, in  itself it is far from conclusive.
Keywords: Head diameter; Sexual dimorphism; Femur; Jamnagar region